Kroppsminne och kollektiv erfarenhet: Objektiveringens betydelse för produktionen av arbetarlitteraritet - Agrell, Beata (Scandinavistica Vilnensis, 2023)
Literature is the memory of a culture: whether included in the canon or not, it testifies to conceptions, mentalities, and conditions in its time. Working-class literature is a young literary type, that for long was excluded from the canon and recognized literary tradition, and therefore has a special relationship to memory, experience, and culture. The first Swedish working-class writers were self-taught, without access to the bourgeois cultural heritage. They were workers, writing about workers, for workers and addressing the class collective. But they were also individuals, who started from their own memories and experiences. How did they go about making their own thing a matter for the whole class? How did they integrate the personal into a collective memory culture? That is the main issue in my article. The task is to shed light on the relationship between individual experience and collective memory in the first generation of Swedish working-class prose around 1910.I will dive into this subject matter by employing the notion of literary objectification, understood as creating vivid images, scenes, and situations from personal memories and experiences serving as an objective correlate (T.S. Eliot). The function of this correlate is to evoke recognition at a distance in the implied reader: an alienated recognition (Viktor Shklovsky), or a kind of sustained Verfremdung (Bertolt Brecht), which also includes contemplation and reflection. A working objective correlate, as I understand it here, must be based on some form of collective memory. I want to develop this idea with the support of memory studies, specifically, works by cultural researcher Jan Assmann and phenomenologist Thomas Fuchs.The reasoning will then be tested on some text examples from the working-class authors Dan Andersson (1888–1920), Maria Sandel (1870–1927), and Karl Östman (1876–1953). In particular, I will dwell on depictions of physical labour, the body memories that are objectified, and the extent to which such objectification produces a special proletarian literariness.
Keywords: Working-class literature; phenomenology; habitus; J. Assmann; collective memory; body memory; objective correlate; T. Fuchs; T. S. Eliot